Nanostructured Strategies for Melanoma Treatment—Part I: Design and Optimization of Curcumin-Loaded Micelles for Enhanced Anticancer Activity - Valentina Paganini; Andrea Cesari; Silvia Tampucci; Patrizia Chetoni; Susi Burgalassi; Michele Lai; Giulia Sciandrone; Silvia Pizzimenti; Fabio Bellina; Daniela Monti (Pharmaceuticals)
Background/Objectives: Melanoma is a pathology that affects a large part of the population, and the currently available therapies have many limitations, including the selective targeting of the site of action. This study explores the development of curcumin (CUR)-loaded nanostructured delivery systems for topical melanoma treatment, addressing CUR’s limitations in bioavailability, solubility, and stability. Methods: Binary surfactant mixtures of Vitamin E-TPGS (TPGS) and Kolliphor ELP (ELP) were selected to form stable micelles for curcumin encapsulation. A Design of Experiments (DoE) approach was applied to optimize the surfactant ratios for enhanced drug solubilization and improved cytotoxic effects on melanoma cells. The final formulation was characterized using Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), and Nuclear Magnetic Resonance (NMR) spectroscopy to confirm its properties. Results: The final formulation, TPGS30ELP15, contained 30 mM TPGS and 15 mM ELP and led to formation of nanostructures of the expected size (hydrodinamic diameter, Dh: 13.11 ± 0.01 nm; polydispersivity index, PDI = 0.371 ± 0.05), able to solubilize 5.51 ± 1.09 mM CUR. The formulation was stable for a 120-day period stored at 4 °C and room temperature in the dark. Cytotoxicity testing in A375 melanoma cells demonstrated that curcumin-loaded micelles significantly reduced cell viability compared to free curcumin. Long-term exposure (24 h) revealed that free curcumin caused an 85% reduction in cell viability, while TPGS30ELP15 resulted in a 70% reduction. Additionally, free curcumin induced a 30% increase in cytoplasmic area, indicating necrosis, whereas TPGS30ELP15 decreased the cytoplasmic area by 20%, suggesting apoptosis. Conclusions: This study demonstrates that TPGS30ELP15 nanomicelles enhance curcumin’s anticancer effects while promoting apoptosis and minimizing necrosis, which is associated with lower inflammation and tissue damage. These findings suggest that TPGS30ELP15 offers a more favorable therapeutic profile for melanoma treatment, paving the way for safer and more effective topical therapies.